Los riesgos laborales en las instituciones privadas debido a la presencia del COVID-19. - Freire Ortiz, Ernesto Olmedo (2022)
This investigative has been taken into consideration by the national and international regulations committee. The aim is to demonstrate that Resolution MDT-2020-023 violates the constitutional and universal rights of workers who are infected with COVID -19 in the workplace. This resolution is deplorable and unconstitutional. It also opposes the rights of workers due to occupational hazards. The Constitution of the Republic of Ecuador and the International Labor Organization, through its regulations, recognize the right of workers to carry out their work activities in a healthy and adequate environment, guaranteeing health, safety, and hygiene. In addition, the right to compensation or medical assistance It's taken into consideration by the social security department. Workers are given this consideration because of the occupational risks they face. This responsibility is absolute and should be placed on the employer. Since COVID-19 is new worldwide, it should be considered within the legal-labor field as a work risk. The purpose of this research is to promote and raise awareness that pathology should be incorporated into the list of occupational diseases in national and international legislation so that in this way, the rights of workers regarding occupational risks aren't violated. Resolution No. MDT-2020 -023 founded by the Ministry of Labor, also recommending that it be declared unconstitutional and have no effect in the labor sector. This research is structured in two main parts: the first is called theoretical framework that contains the following units: The rights of workers and occupational hazards, safety and hygiene in the workplace, COVID-19 in occupational hazards. The second part is a well-structured investigative methodology.